Unilateral Versus Bilateral Spreader Grafts to Correct Cartilaginous Deviations in Structural Rhinoplasty: A Comparative Study on the Aesthetic and Functional Outcomes - Gimeno-Torres, Laura; Calvo-Gómez, Jordi; Pérez-Carbonell, Tomàs; Roselló, María V.; Vallejo-García, Alejandro; Marrero-Pérez, Juan C.; Marco-Algarra, Jaime (Facial Plastic Surgery, 2025)
Spreader grafts (SG) are used in rhinoplasty to correct cartilaginous deviations. There are no studies that compare aesthetic and functional outcomes of unilateral (USG) and bilateral SG (BSG).Compare whether USG or BSG is better to correct cartilaginous deviations, if there are differences in dorsal width ratio (DWR) and in patient-perceived aesthetic and functional outcomes.Retrospective study of 35 patients who underwent septorhinoplasty with USG or BSG. Deviation angle and DWR were calculated in frontal images before and 6 months postsurgery. Aesthetic and functional results were measured using nasal obstruction symptom evaluation (NOSE) and visual analog scales (VAS).BSG significantly improved postoperative nasal deviation compared to USG (179.6 degrees vs. 172.9 degrees; p < 0.05). In minor preoperative deviations, there were no significant differences between BSG and USG (179.57 degrees vs. 177 degrees, respectively; p > 0.05). In major preoperative deviations, BSG provided better correction (179.62 degrees vs. 170.5 degrees; p < 0.05). DWR increased more with BSG compared to USG (0.12 vs. 0.04; p < 0.05). VAS and NOSE scores were similar in both groups.BSG is more effective in correcting major cartilaginous deviations, while both USG and BSG effectively correct minor deviations. Though BSG increases DWR, this does not negatively impact patient-perceived aesthetic or functional outcomes.
Keywords: spreader grafts; functional septorhinoplasty; crooked nose; nasal deviation; dorsal width